A pulse coherent nqr spectrometer with effective transient suppression - Хандожко, Александр Григорьевич; Хандожко, Виктор Александрович; Самила, Андрей Петрович (Eastern-European Journal of Enterprise Technologies, 2013)
The presence of the quadrupole moments of isotopes of gallium and indium in GaSe and InSe allows applying the radiospectroscopy of nuclear quadrupole resonance (NQR) for studying of the crystal structures of these compounds. The structure of the pulse coherent spectrometer with a minimum number of functional nodes is proposed. The source of carrier frequency, oscillations is the frequency synthesizer for filling the probe pulses in the range of NQR resonance frequencies 2 ÷ 50 MHz (isotopes 14N, 69Ga, 71Ga, 113In, 115In). The nuclear spin induction signal after the amplification is fed to a synchronous detector, made on the balanced mixer. The output power amplifier on the field-effect transistor MRF6VP11KH develops an excitation pulse power up to 1 kW in the receiving coil. Restoration of the NQR spectrum of the spin induction signal is carried out by the fast Fourier transform method. The circuit solutions on the elimination of the receiving coil "ringing" of oscillating circuit of spectrometer and transient suppression in the receive path of the NQR pulse radio spectrometer are proposed. Safe closing of the receive path in the pauses between probe pulses (up to 100 dB for the carrier frequency) is provided by the scheme of three similar cascades on the dual-gate FET.